Genotyping and phylogenetic analysis of Fasciola species in animals from Iraq using the ITS1 marker - Hama, Abdullah A (The Journal of Infection in Developing Countries, 2025)
Introduction: Fasciola species are trematodes primarily infecting the liver and bile ducts of animals and humans, and causing serious lesions. They have significant medical and economic impacts, leading to chronic illness and reduced productivity in livestock. This study aimed to assess the genetic diversity of liver flukes isolated from domestic ruminants in Sulaimani province in Iraq. Methodology: A total of 100 fecal samples were collected from animals living in local farms, including sheep (n = 44), goats (n = 36), and cattle (n = 20). Additionally, 42 liver flukes were obtained from 21 slaughtered animals (10 sheep, 6 cattle, and 5 goats) at the Sulaimani abattoir; 2 flukes per host were collected. DNA was extracted from sedimentation-positive fecal samples and from fluke tissue. Molecular characterization was performed by polymerase chain reaction (PCR) of the internal transcribed spacer 1 (ITS1), and subsequent restriction fragment length polymorphism (RFLP) using RsaI and Tsp509I endonucleases. Genetic diversity was assessed through sequence comparison and phylogenetic analysis. Results: RFLP analysis revealed 3 distinct patterns among liver flukes. DNA sequencing and phylogenetic analysis revealed 3 main clusters, primarily consisting of Fasciola hepatica, Fasciola gigantica, and Fasciola intermediate. Conclusions: The study demonstrates that PCR-RFLP of ITS1 with RsaI is effective for distinguishing F. hepatica from F. intermediate, while Tsp509I is useful for differentiating F. hepatica from F. gigantica. Additionally, PCR-RFLP of the ITS1 is a simple, fast, and reliable method for species identification of liver flukes present in fecal samples of animals, and directly from fluke tissue.